Edaphic controls on ecosystem‐level carbon allocation in two contrasting Amazon forests. Issue 9 (16th September 2014) - Jiménez, Eliana M.; Peñuela‐Mora, María Cristina; Sierra, Carlos A.; Lloyd, Jon; Phillips, Oliver L.; Moreno, Flavio H.; Navarrete, Diego; Prieto, Adriana; Rudas, Agustín; Álvarez, Esteban; Quesada, Carlos A.; Grande‐Ortíz, Maria Angeles; et al.
Abstract Studies of carbon allocation in forests provide essential information for understanding spatial and temporal differences in carbon cycling that can inform models and predict possible responses to changes in climate. Amazon forests play a particularly significant role in the global carbon balance, but there are still large uncertainties regarding abiotic controls on the rates of net primary production (NPP) and the allocation of photosynthetic products to different ecosystem components. We evaluated three different aspects of stand‐level carbon allocation (biomass, NPP, and its partitioning) in two amazon forests on different soils (nutrient‐rich clay soils versus nutrient‐poor sandy soils) but otherwise growing under similar conditions. We found differences in carbon allocation patterns between these two forests, showing that the forest on clay soil had a higher aboveground and total biomass as well as a higher aboveground NPP than the sandy forest. However, differences between the two forest types in terms of total NPP were smaller, as a consequence of different patterns in the carbon allocation of aboveground and belowground components. The proportional allocation of NPP to new foliage was relatively similar between them. Our results of aboveground biomass increments and fine‐root production suggest a possible trade‐off between carbon allocation to fine roots versus aboveground compartments, as opposed to the most commonly assumed trade‐off between total aboveground and belowground production. Despite these differences among forests in terms of carbon allocation, the leaf area index showed only small differences, suggesting that this index is more indicative of total NPP than its aboveground or belowground components.